Alcohol consumption and use of health care services in people with severe mental illness and stressful childhood experiences. Issue 2 (3rd April 2017) - Schneeberger, Andres R.; Huber, Christian G.; Seixas, Azizi; Muenzenmaier, Kristina H.; Lang, Undine E.; Castille, Dorothy; Larkin, Stefan; Link, Bruce G.
ABSTRACT: People who suffer from severe mental illness often present with histories of abuse during childhood. Alcohol use disorders is a common co-morbidity of survivors of childhood abuse and neglect. This study analyzes the effects of stressful childhood experiences, a proxy for trauma, on the frequency of alcohol consumption and the utilization of health care services in a population of people with severe mental illness. There were 111 men (mean age: 35 years) and 72 women (mean age: 40.0 years) with severe mental illness that were recruited from psychiatric outpatient clinics in New York City. The analysis focused on lifetime prevalence of stressful childhood experiences, alcohol consumption, and utilization of health care services over time. The longitudinal data were analyzed over 12 months with a level-2 model (multilevel modeling). Out of the participants, 41.5% reported a history of more than four types of abusive experiences. There were 33.3% that had a DSM-IV diagnosis of alcohol abuse and 27.3% qualified for the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition diagnosis of alcohol dependence throughout their lives. Stressful childhood experiences predicted an increased frequency of alcohol consumption over time. People with histories of childhood abuse had more often been to outpatient clinics and 12-step programs, but at the same time showed lower frequency rates of psychiatrist visits and visits to outpatient clinics. Childhood abuse is prevalent in people with severe mental illness and is related to an increased alcohol consumption. Despite an increased need of health care services, affected persons might encounter more barriers to access them.